2022
DOI: 10.1159/000522481
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Development of Major Adverse Cardiac Events following Percutaneous Coronary Intervention

Abstract: <b><i>Background:</i></b> Coronary artery disease remains the greatest cause of morbidity and mortality worldwide despite the growing access to percutaneous coronary intervention (PCI). Data regarding the factors predicting the development of major adverse cardiac events (MACE) in patients undergoing PCI are, however, lacking in the gulf region. In this study, we analyze demographics and risk profile of all patients undergoing PCI in a tertiary cardiovascular center located in Dubai – U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It has been reported that patients with STEMI and DM had higher hypertension, hyperlipidemia, left main coronary artery disease, and higher in-hospital mortality rates [8]. DM is an independent predictor of major adverse cardiac events in patients after PCI [9]. Pathophysiological processes underlying the development and determining the course of AMI in diabetic patients demand a thorough and comprehensive examination in order to reduce the risk of adverse recurrent cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that patients with STEMI and DM had higher hypertension, hyperlipidemia, left main coronary artery disease, and higher in-hospital mortality rates [8]. DM is an independent predictor of major adverse cardiac events in patients after PCI [9]. Pathophysiological processes underlying the development and determining the course of AMI in diabetic patients demand a thorough and comprehensive examination in order to reduce the risk of adverse recurrent cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%